Pulverised natural dyes for textile dyeing - Feroza Ahmad, Faiz (Universiti Malaysia Sarawak (UNIMAS), 2015)
Natural dyes are an alternative to synthetic dyes as they are eco-friendly and not hazardous to health. However, the conventional way of natural dyeing is a complex process which lack of convenience in terms of preparation and storage as the fresh plant materials need to be processed as soon as possible in order to prevent them from getting mouldy or rotting. Therefore in this research, the plant materials have been converted into pulverised dyes using the dry pulverisation technique, as the dried materials are expected to be more practical, economical and have longer shelf life. This study aims to improve the natural dyeing recipe with better lightfastness and colourfastness using the pulverised plants which can be used as a guide for dyers or textile craft producers. A total of 10 types of plants involved in the experiments using100% silk and cotton fabrics. Other materials used in the dyeing experiments are mordants such as Alum (Aluminium Ammonium Sulphate), “Tawas” (Aluminium Potassium Sulphate), Limewater (Calcium Hydroxide) and an antioxidant additive namely Vitamin C (Ascorbic Acid). The techniques used were pre-mordanting and direct dyeing, followed by Vitamin C aftertreatment utilising the immersion method. The lightfastness of the dyed and aftertreated fabric samples was observed after 40 hours exposure to direct sunlight. Subsequently, advanced experiments were conducted using “Sepang” wood (Caesalpinia sappan), “Engkerabai” (Psychotria viridiflora) and “Ketapang” leaves (Terminalia catappa), representing three different colours of the pulverised dyes. The effect of different amount of mordant and dyes on colour intensity, Vitamin C aftertreatment and lightfastness tests was further observed where the result shows that the fabric type, the dyeing properties together with the dyebath concentration and amount of mordant will determine the colourfastness and lighfastness quality of pulverised plant dyes. More importantly, the research has discovered that the fabric samples with Vitamin C aftertreatment especially for silk exhibited slower rate of fading as compared to non-treated fabric samples. This shows that Vitamin C is an effective agent in improving the lightfastness of pulverised plant dyes produced in this research namely mangosteen (Garcinia mangostana), mangrove / “Tengar” (Ceriops tagal), “Mengkudu” (Morinda citrifolia), betel nut (Areca catechu), Ebony spleenwort (Asplenium platyneuron), “Ketapang” (Terminalia catappa), henna (Lawsonia inermis) and “Engkerabai” leaves (Psychotria viridiflora). However, Vitamin C has reversed effect if used on onion skins (Allium cepa) and “Sepang” wood. Therefore, due to its enhancing and discharging characteristics, Vitamin C has the potential to increase the practicality in natural dyeing as it can be used to change the intensity of colour in creating textile patterns.